KONSEP MASLAHAH MENURUT IMAM MALIK DAN ALTUFI (STUDI KOMPARATIF TENTANG MASLAHAH IMAM MALIK DAN NAJM AL-DIN AL-TUFI) - Imas Setiyawan (Sekolah Tinggi Agama Islam Taruna Surabaya, 2020)
Among the sources of Islamic law which is still disputed by scholars’ argumentis maslahah. Some scholars reject it, but most agree make maslahah as one of the sources of Islamiclaw in matters of ijtihad. Imam Malik considered as a pioneer scholar who makes maslahah as onesource of law ijtihadnya. His view was followed by the scholars 'other, one of whom is Najm al-Din al-Tufi, a cleric' Hambali. However, the twoleaders of thought are not the same, even in certaincases the difference is very sharp, although in certain parts have in common. In the view of Malik,maslahah serve as asource of Islamic law in matters which are not discussed formallyby nas and ijma ', butmust not conflict with the spirit of the passage as a whole. In contrast, al-Tufi maslahahgood use in the problem discussed by nat/ijma ', or not. As for the area applicationsmaslahah, both agree that that maslahah only be used in matters mu'amalah.